The Short Form of the Glasgow Composite Measure Pain Scale in Post-operative Analgesia Studies in Dogs: A Scoping Review - Testa, Barbara; Reid, Jacqueline; Scott, Marian E.; Murison, Pamela J.; Bell, Andrew M. (Frontiers in Veterinary Science, 2021)
The measurement and treatment of acute pain in animals is essential from a welfare perspective. Valid pain-related outcome measures are also crucial for ensuring reliable and translatable findings in veterinary clinical trials. The short form of the Glasgow Composite Measure Pain Scale (CMPS-SF) is a multi-item behavioural pain assessment tool, developed and validated using a psychometric approach, to measure acute pain in the dog. Here we conduct a scoping review to identify prospective research studies that have used the CMPS-SF. We aim to describe the contexts in which it has been used, verify the correct use of the scale, and examine whether these studies are well designed and adequately powered. We identify 114 eligible studies, indicating widespread use of the scale. We also document a limited number of modifications to the scale and intervention level, which would alter its validity. A variety of methods, with no consensus, were used to analyse data derived from the scale. However, we also find many deficiencies in reporting of experimental design in terms of the observers used, the underlying hypothesis of the research, the statement of primary outcome, and the use of a priori sample size calculations. These deficiencies may predispose to both type I and type II statistical errors in the small animal pain literature. We recommend more robust use of the scale and derived data to ensure success of future studies using the tool ensuring reliable and translatable outcomes.